PRACTICES OF SUCCESSFUL EMPLOYMENT OF THE YOUTH - N. I. PROKOPOV; S. N. ANTONYUK; S. Yu. IVANOV; D. V. IVANOVA (Высшее образование в России)
The article analyzes the state and the trends of youth employment, identifies the main trends in the development of social and labor relations in the context of financial and economic instability. The authors determine the key directions of formation of demand for university graduates on the regional labor market are determined. The work highlights the results of the authors’ sociological study of employment problems of young professionals, describes the issues of interaction of University with employers. Particular attention is drawn to the requirements of modern employers to young professionals, the development of measures to manage the employment and adaptation of young people on the labour market. The paper identifies measures to increase the level of future young specialist involvement in social partnership relations between the University and the employers. The article gives practical recommendations on optimization of interaction between employers and representatives of universities in the context of improving the quality of educational services.